2012
DOI: 10.1074/jbc.m112.386060
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Modulates Respiratory Complex I Activity in Response to Acute Mitochondrial Dysfunction

Abstract: Background: How are mitochondrial functions regulated in response to mitochondrial defects? Results: Acute OXPHOS defects lead rapidly to a glucose-dependent repression of complex I activity. Conclusion: We discovered an "emergency shutdown" system adapting respiratory chain function to mitochondrial defects. Significance: This study reveals a novel type of metabolic regulation that could open the way to medically useful alterations of OXPHOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 40 publications
(41 reference statements)
1
49
0
Order By: Relevance
“…Deregulation of mitochondrial respiratory chain Complex I activity is a common cause of metabolic disorders [8,29,30]. In an attempt to understand the mechanisms underlying the protective effects of apigenin on BAECs, we examined whether apigenin could modulate Complex I activity following LPS stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Deregulation of mitochondrial respiratory chain Complex I activity is a common cause of metabolic disorders [8,29,30]. In an attempt to understand the mechanisms underlying the protective effects of apigenin on BAECs, we examined whether apigenin could modulate Complex I activity following LPS stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…AOX limits excess ROS production (Cannino et al, ; Sanz, Fernández‐Ayala, Stefanatos, & Jacobs, ) and attenuates responses to ROS (Dogan et al, ; El‐Khoury et al, ; Hakkaart et al, ). We are not aware of any studies indicating disruption of pupal development by global treatment with antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have indicated that Ndi1 could rescue Complex I dysfunction by facilitating electron transport from NADH to coenzyme Q without generating additional ROS (19, 20). We find that bypassing Complex I could improve mtROS in podocytes and tubular cells exposed to HG conditions suggesting that Complex I dysfunction is an important contributor to the increased mtROS in the HG environment.…”
Section: Discussionmentioning
confidence: 99%